Kreasi Pengetahuan dan Inovasi pada Industri Kreatif Batik di Empat Daerah Industri Batik di Jawa - H.M. Ismail (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Knowledge creation is very important engine of innovation and competitive advantage. But regardless of its importance, not many study has been done in this field. This study conducted in batik companies located in four area in Java to reveal why these companies survival. Aside from that, the process of knowledge creation in these companies will become an important for building of knowledge management theory and practices in the companies.Keywords: Knowledge creation, batik companies